2020
DOI: 10.1111/jvs.12919
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between epixylic bryophyte communities and microclimate

Abstract: Aim Dead wood‐inhabiting bryophyte communities are formed by several important factors. Besides the amount, quality and continuity of the substrate, there are also external factors indirectly influencing their structure. One of the most important is local microclimate. This fact has been recognized by many previous authors, yet studies exploring the direct effect of the microclimate on epixylic bryophytes are still sparse. Based on directly measured values of local temperature, air humidity and canopy openness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Our study supported the hypothesis that habitat niche breath affects species’ vulnerability to climate change (cf., MacLean & Beissinger, 2017): the total habitat suitability for obligate deadwood species in Sweden decreased, whereas that for facultative species increased. Táborská et al (2020) similarly found that epixylic specialists in temperate forests were associated with low temperatures. Most likely, for obligate deadwood specialists, the loss of habitat at the (southern) trailing‐edge cannot be balanced by a gain of habitat at the leading‐edge, because the latter critically depends on the concomitant range shifts of suitable host trees (cf., Berg et al, 2010; Buckley & Kingsolver, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study supported the hypothesis that habitat niche breath affects species’ vulnerability to climate change (cf., MacLean & Beissinger, 2017): the total habitat suitability for obligate deadwood species in Sweden decreased, whereas that for facultative species increased. Táborská et al (2020) similarly found that epixylic specialists in temperate forests were associated with low temperatures. Most likely, for obligate deadwood specialists, the loss of habitat at the (southern) trailing‐edge cannot be balanced by a gain of habitat at the leading‐edge, because the latter critically depends on the concomitant range shifts of suitable host trees (cf., Berg et al, 2010; Buckley & Kingsolver, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…study supported the hypothesis that habitat niche breath affects species' vulnerability to climate change (cf.,MacLean & Beissinger, 2017): the total habitat suitability for obligate deadwood species in Sweden decreased, whereas that for facultative species increased Táborská et al (2020). similarly found that epixylic specialists in temperate forests were associated with low temperatures.…”
mentioning
confidence: 90%
“…This can be explained by a corresponding decrease of air moisture. Some species, especially true epixylics, have been reported to be drought-sensitive (Söderström, 1988b;Laaka, 1993;Proctor et al, 2007;Táborská, Kovács, Németh, and Ódor, 2020;Kropik et al, 2021). High water availability in deadwood is important for spore germination of epixylic bryophytes (Wiklund and Rydin, 2004).…”
Section: Ecologymentioning
confidence: 99%
“…This site is the oldest, with less logging area, and presents the highest humidity compared with the rest of the evaluated management sites. An old forest keeps conditions such as humidity and unique subtracts necessary for some species [104,105]. Other studies in boreal forests indicated that differences in the intensity disturbance could change the bryophytes species composition over time [106].…”
Section: Diversity and Community Moss Structurementioning
confidence: 99%